Informing the Design of a New Pragmatic Registry to Stimulate Near Miss Reporting in Ambulatory Care. Issue 3 (April 2021) - Pfoh, Elizabeth R.; Engineer, Lilly; Singh, Hardeep; Hall, Laura Lee; Fried, Ethan D.; Berger, Zackary; Wu, Albert W.
Abstract : Objective: Ambulatory care safety is of emerging concern, especially in light of recent studies related to diagnostic errors and health information technology-related safety. Safety reporting systems in outpatient care must address the top safety concerns and be practical and simple to use. A registry that can identify common near misses in ambulatory care can be useful to facilitate safety improvements. We reviewed the literature on medical errors in the ambulatory setting to inform the design of a registry for collecting near miss incidents. Methods: This narrative review included articles from PubMed that were: 1) original research; 2) discussed near misses or adverse events in the ambulatory setting; 3) relevant to US health care; and 4) published between 2002 and 2013. After full text review, 38 studies were searched for information on near misses and associated factors. Additionally, we used expert opinion and current inpatient near miss registries to inform registry development. Results: Studies included a variety of safety issues including diagnostic errors, treatment or management-related errors, communication errors, environmental/structural hazards, and health information technology (health IT)–related concerns. The registry, based on the results of the review, updates previous work by including specific sections for errors associated with diagnosis, communication, and environment structure and incorporates specific questions about the role of health information technology. Conclusions: Through use of this registry or future registries that incorporate newly identified categories, near misses in the ambulatory setting can be accurately captured, and that information can be used to improve patient safety. Abstract : Supplemental digital content is available in the text.